Perspektif Yuridis Pengembalian Kerugian Keuangan Negara Dalam Tindak Pidana Korupsi - A. Djoko Sumaryanto (Fakultas Hukum Universitas Bhayangkara Surabaya, 2010)
Corruption eradication in Indonesia has been worked out through the various way and form either in the field of law or the policy or criminal law. Law reformation in the form of corruption eradication not only concern with the reformation of code/law, but it also concern with enforcement and law structure. There is much difficulty to eradicate corruption. However, it doesn’t mean that it is impossible to work it out and retrieve public finance asset or property. Through this study, the writer wants to research public finance and ways to eradicate corruption and retrieve state finance as well by using various instruments, either penal or non penal.